2022
DOI: 10.3390/ijms23052667
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Gut Microbiota Combined with Upregulation of Intestinal Tight Junction Explains Anti-Inflammatory Effect of Corylin on Colitis-Associated Cancer in Mice

Abstract: Inflammatory bowel disease (IBD) involves chronic inflammation, loss of epithelial integrity, and gastrointestinal microbiota dysbiosis, resulting in the development of a colon cancer known as colitis-associated colorectal cancer (CAC). In this study, we evaluated the effects of corylin in a mouse model of dextran sodium sulfate (DSS)-induced colitis. The results showed corylin could improved the survival rate and colon length, maintained body weight, and ameliorated the inflammatory response in the colon. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 66 publications
(73 reference statements)
2
15
0
1
Order By: Relevance
“…Intestinal epithelial cells (IECs) formed various kinds of mucosal layers separating gut microbes and immune cells to prevent the following overreaction of inflammation, which can be viewed as a critical barrier to intestinal homeostasis. It has been proven that dysbiosis is associated with intestinal inflammation in animal models of colitis [ 43 ]. Still, studies have also found that both declines of tight junction proteins (like ZO-1, claudin-1, occludin) and increasing permeability (leaky gut) appear forward to severe gut inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal epithelial cells (IECs) formed various kinds of mucosal layers separating gut microbes and immune cells to prevent the following overreaction of inflammation, which can be viewed as a critical barrier to intestinal homeostasis. It has been proven that dysbiosis is associated with intestinal inflammation in animal models of colitis [ 43 ]. Still, studies have also found that both declines of tight junction proteins (like ZO-1, claudin-1, occludin) and increasing permeability (leaky gut) appear forward to severe gut inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The role of Romboutsia in gut inflammation remains unclear. In some studies, Romboutsia was considered as beneficial bacteria in acute colitis [ 75 ], but its enrichment was in DSS-induced chronic colitis [ 76 , 77 ] and azoxymethane (AOM)/DSS-induced colitis-associated cancer (CAC) [ 78 ]. Consistent with an aforementioned study [ 78 ], our results showed that DSS could increase Romboutsia abundance.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, Romboutsia was considered as beneficial bacteria in acute colitis [ 75 ], but its enrichment was in DSS-induced chronic colitis [ 76 , 77 ] and azoxymethane (AOM)/DSS-induced colitis-associated cancer (CAC) [ 78 ]. Consistent with an aforementioned study [ 78 ], our results showed that DSS could increase Romboutsia abundance. Klebsiella , a pathogen belonging to the family Enterobacteriaceae , was significantly more abundant in the gut of mice with DSS-induced colitis [ 79 , 80 ] and played a key role in pathological damage initiation and perpetuation in various intestinal inflammations and cancers [ 57 , 81 , 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are no reports about the relationship between Patescibacteria and PD. Patescibacteria is an interesting but currently not widely understood anaerobic bacterium [ 33 ]. In the cerebral cortex and hippocampus of a rat model of chronic unpredictable mild stress (CUMS), Zhang et al found that it was positively associated with 5-hydroxy tryptamine (5-HT), brain-derived neurotrophic factor (BDNF), and glucagon-likepeptide-1 (GLP-1) [ 34 ].…”
Section: Discussionmentioning
confidence: 99%